Pediatric unicystic cystic partially differentiated nephroblastoma: The first case report - Chao, Liu; Lei, Zhang; Xiang, Li; Qi, Zhou (Frontiers in Pediatrics, 2022)
Cases of patients with cystic partially differentiated nephroblastoma (CPDN) have been reported to date, which presented as polycystic renal tumor in all of them. It is a special pathological type of nephroblastoma. Here, we report the first case of a unicystic CPDN in a child. The patient was diagnosed with a simple renal cyst and underwent laparoscopic decortication. The naive nephron was found in the pathological section, and the diagnosis of CPDN was confirmed. The patient then underwent a radical nephrectomy and six cycles of postoperative chemotherapy. There was no recurrence or metastasis after 2 years of follow-up. Pediatric CPDN presenting as a unicystic renal tumor poses a new challenge to the diagnosis, differential diagnosis, and treatment of unicystic renal tumor.